PENGARUH MOTIVASI KEDISIPLINAN DAN KEPEMIMPINAN TERHADAP PRESTASI KERJA PETUGAS KEBERSIHAN - Afrinaldy Rustam (Sosial Budaya, 2016)
Duty by Institution at duty Market, Hygiene and Gardening is the development of hygiene area and beauty of urban region. this Area development is maximally hence from Environment Ministry will give the appreciation in the form of " Appreciation Adipura". Research On duty Market, Hygiene And Gardening of Kampar representing government organization which obliged to give the service as well as possible to society. Special for the hygiene of Bangkinang required a Hygiene Officer which with quality and delay comprehending its function as hygiene officer reaching of cleanest town so that get the Appreciation of Adipura of hygiene area. In line with formula of is problem of and target of research hence method analyse the data used in this research Doubled Analysis Regretion where Coefficient of regretion variable motivate the (X1) = 0,137 this show the level of the variable influence to labour capacity. Koefisen Regresi of leadership variable (X3) = 0,364. this show the level of the variable influence to labour capacity. For the Coefficient of regresi 0,776 representing constant value showing positive sign with the meaning without existence of variable motivate the, discipline and leadership hence labour capacity will go up equal to 0,776 times.